Survival and cardiovascular events in men treated with testosterone replacement therapy: an intention-to-treat observational cohort study. Issue 6 (June 2016) - Wallis, Christopher J D; Lo, Kirk; Lee, Yuna; Krakowsky, Yonah; Garbens, Alaina; Satkunasivam, Raj; Herschorn, Sender; Kodama, Ronald T; Cheung, Patrick; Narod, Steven A; Nam, Robert K
Summary: Background: Conflicting evidence exists for the association between testosterone replacement therapy and mortality and cardiovascular events. The US Food and Drug Administration recently cautioned that testosterone replacement therapy might increase risk of heart attack and stroke, based on evidence from studies with short treatment duration and follow-up. No previous study has assessed the effect of duration of testosterone treatment on these outcomes. We aimed to assess the association between long-term use of testosterone replacement therapy and mortality, cardiovascular events, and prostate cancer diagnoses, using a time-varying exposure analysis. Methods: We did a population-based matched cohort study of men aged 66 years or older newly treated with testosterone replacement therapy and controls matched for age, region of residence, comorbidity, diabetes status, and index year from 2007–12 in Ontario, Canada, using data from the Ontario Drug Benefit database, the Canadian Institute for Health Information (CIHI) Discharge Abstract Database, the CIHI National Ambulatory Care Reporting System, the Ontario Health Insurance Plan database, the Ontario Myocardial Infarction Database, the Ontario Diabetes Database, the Ontario Cancer Registry, and the Registered Persons database. We assessed the association between cumulative testosterone replacement therapy exposure and mortality, cardiovascular events, and prostate cancer using marginal models with a time-varying testosterone exposure. Findings: We included 10 311 men treated with testosterone replacement therapy and 28 029 controls between Jan 1, 2007, and June 30, 2012. Over a median follow-up of 5·3 years (IQR 3·6–7·5) in the testosterone replacement therapy group and 5·1 years (3·4–7·4) in the control group, patients treated with testosterone replacement therapy had lower mortality than did controls (hazard ratio [HR] 0·88, 95% CI 0·84–0·93). Patients in the lowest tertile of testosterone exposure had increased risk of mortality (HR 1·11, 95% CI 1·03–1·20) and cardiovascular events (HR 1·26, 95% CI 1·09–1·46) compared with controls. By contrast, those in the highest tertile of testosterone exposure had decreased risk of mortality (HR 0·67, 95% CI 0·62–0·73) and cardiovascular events (HR 0·84, 95% CI 0·72–0·98), with a significant trend across tertiles (p<0·0001). Risk of prostate cancer diagnosis was decreased for those with the highest tertile of exposure (HR 0·60, 95% CI 0·45–0·80) compared with controls, but not for those with the shortest exposure. Interpretation: Long-term exposure to testosterone replacement therapy was associated with reduced risks of mortality, cardiovascular events, and prostate cancer. However, testosterone replacement therapy increased the risk of mortality and cardiovascular events with short durations of therapy. In view of the limitations of observational data and the potential for selection bias, these results warrant confirmation in a randomised trial. Funding: Physicians' Services Incorporated Foundation and Ajmera Family Chair in Urologic Oncology.